Patterns of language choice and use among undergraduates of different ethnic groups in a malaysian public university - Md. Mostafizar Rahman, Abu Rashed (2007)
Language choice and use are sociolinguistic phenomena. The choice and use of language refers to selecting languages for different purposes in different contexts. In a bi-/multilingual society, these phenomena are very important issues. Fishman’s (1972) domain analysis is used to investigate the choice of language in a multilingual context in this study. The analysis answers questions directed at ‘who speaks what language to whom, when, where and even why’. In answering these questions, a host of variables come into play. These variables are language planning and policy, language user’s social background, linguistic profile, profession, educational background, and social domains. The objectives of this study were to identify UPM undergraduates’ patterns of language choice and use in the domains of family, friendship, neighborhood, transaction, education, office, religion and media; and to investigate the effect of ethnicity, gender, discipline of study and proficiency on their patterns of language choice and use. Data for the study were collected through a questionnaire survey administered to 300 UPM undergraduates. The analysis of data was done both quantitatively and qualitatively. SPSS was used to get percentage values and frequencies through descriptive statistics and correlations between variables were obtained through Chi-square tests. The strength of relationship was measured using Contingency Coefficient and the relationship was interpreted with reference to Guilford’s rule of thumb. Findings of the study indicate that the informants chose and used different languages in different domains with consideration to the status of the domains. They were found to use ethnic languages in those domains which were more informal and intimate such as family, religion and media. Bahasa Melayu and English were chosen in more formal domains such as education and office. In the patterns of language choice among the informants, the study found the influence of ethnicity and language proficiency in all the domains investigated. The discipline of study was also found to influence language choice partially, while the influence of gender was not found. In short, this study found variation of choice of languages to be constrained and influenced by different factors.